After Molière (1673–1689). (29th August 2022) - Clarke, Jan
Abstract: Molière was, above all, a man of the theatre: an actor and administrator as well his company's chief playwright, his death in 1673 was a blow from which many thought his company would not recover. This article examines the fifteen or so years following his death to determine how his immediate successors overcame the difficulties his death presented in each of these three areas. Above all, we see them struggling to protect his works from the danger of over-familiarity, while casting round to find new comic authors to replace him (including from among their own number). And in so doing, they almost coincidentally laid the foundations of the venerable institution we know today as the 'Maison de Molière'.